Compassion focused therapy for women in the perinatal period: a summary of the current literature - Millard, Leah Alice; Wittkowski, Anja (Frontiers in Psychiatry, 2023)
Introduction: Compassion focused therapy (CFT) is emerging as an effective psychological intervention to treat those experiencing mental health difficulties. CFT was adapted for women who are mothers during the perinatal period (from conception to two year postpartum).Although CFT is being delivered in NHS perinatal mental health services in the United Kingdom (UK), its current evidence-base for the treatment of women's mental health problems is unclear. As part of this Mini Review, we aimed to identify the current findings relating to CFT for women in the perinatal period (with or without a mental health condition) in order to identify any associated future research and clinical implications. Method: A systematic search of two databases was undertaken. Included studies were required to meet the following criteria: 1) offered an intervention using CFT or perinatal CFT (P-CFT), 2) participants were women in the perinatal period and 3) studies used a pre-and postintervention study design. No language restrictions were used. A narrative synthesis was then conducted. Results: Five studies, dating from 2018 to 2023, met the inclusion criteria. A total of 1,258 participants were included across those studies. Significant improvements in compassion-based outcomes (i.e., self-compassion, self-criticism/self-reassurance) were observed. However, these findings were primarily derived from non-clinical samples (n=4) and could only be seen as preliminary. Although these results are encouraging for mothers presenting with sub-clinical mental health symptoms,, further research is clearly warranted to determine whether CFT/P-CFT may benefit mothers, including those presenting with more significant perinatal mental health difficulties.